Effects of pH and NaCl on hydrolysis and transpeptidation activities of a salt-tolerant γ-glutamyltranspeptidase from Bacillus amyloliquefaciens S0904 - Cho, Hye-Bin; Ahn, Jun-Ho; Yang, Hyeon-Gyu; Lee, Jaeick; Park, Wu-Jin; Kim, Young-Wan (Food science and biotechnology, 2021)
Bacillus amyloliquefaciens S0904 was selected as a hyperproducer of a glutamine-hydrolyzing enzyme which was identified as a γ-glutamyltranspeptidase catalyzing both hydrolysis and transpeptidation of glutamyl substrates. The signal peptide-truncated recombinant enzyme (rBAGGT) showed two-fold enhanced specific activity for hydrolysis and optimum pH shift to pH 7 from pH 6 compared with the wild type. The hydrolysis activity of rBAGGT was tolerant against NaCl up to 2.5 M, whereas the transpeptidation activity decreased by NaCl. At pH 6, the addition of 1.5 M NaCl not only enhanced the hydrolysis activity but also inhibited the transpeptidation activity to be ignorable. By contrast, at pH 9 in the absence of NaCl, the alkaline pH-favored transpeptidation activity was 99% of the maximum with only 15% of the maximum hydrolysis activity. In conclusion, the hydrolysis and transpeptidation activities of the recombinant BAGGT is controllable by changing pH and whether or not to add NaCl.